Nükhet Varlik, Plague and Empire in the Early Modern Mediterranean World. The Ottoman Experience, 1347-1600 (Cambridge: Cambridge University Press, 2015) - Jón Þ. Þór (Nordicum-Mediterraneum, 2016)
Book review of: Nükhet Varlik, Plague and Empire in the Early Modren Mediterranean World. The Ottoman Experience, 1347-1600 (Cambridge: Cambridge University Press, 2015), 336pp.